Comparison of bombyx mori l. Fibroin coatings on the mechanical properties of collagen membranes - Fathurrahman, Helmi; Sunarintyas, Siti; Barunawati, Sri Budi; Nuryono, Nuryono (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: Most of dental implants are accompanied by guided bone regeneration (GBR) procedures. Collagen membrane which is the most widely used type of membrane in the GBR procedure has the disadvantage of not having antimicrobial properties, old bone formation, easy to tear, and soft so that it does not maintain the dimensions of the augmentation area. Bombyx mori L. fibroin has good mechanical properties and has the potential to be used as a pharmaceutical material that is biocompatible, antimicrobial, and stimulates bone growth. The aim of this study was to analyze the effect of Bombyx mori L. fibroin coating on the mechanical properties of collagen membranes. Method: The samples consisted of the control group (group A) and the treatment group, the collagen membrane was coated using the Bombyx mori L dip-coating fibroin technique, namely group B (1 time coating process), group C (2 times coating process) and group D (3 times the coating process). Statistical analysis used one-way ANOVA (p